Linking Agriculture Research Extension Education and Farmer (Areef) In Local Level: Municipal Perspectives - Mahesh Jaishi; P. B. Nepali; R.K. Timsina; H. Neupane (CSRC Publishing, Center for Sustainability Research and Consultancy Pakistan, 2022)
Purpose: The main research issue of study is to identify the nature of existing linking mechanisms among AREE institutions at municipality level affecting the agriculture service delivery. Study also focused to explore the possibilities of university-community engagement to strengthen the linkage gaps. Design/Methodology/Approach: Convergent parallel mix methods design along with systematic review was employed to attain the study objective. Ten observation of service delivery embedded with KIIs were conducted in five Rural-Municipalities and five Municipalities. The theoretical framework was discussed to improve the current linkage interface at local level Findings: The literature from systematic review showed, top-down research and extension management, fragmented research, extension, and academic institutions, lower perception of the value of linkage, poor infrastructure of basic services, absenteeism of human resource, and with inadequate competencies were the main causes of weak research, extension, education, and farmer linkages at the local level. Implications/Originality/Value: The paper discussed and conceptualize various linkage modalities that are being practiced over the country must be contextualize based on the characteristics of agriculture research, extension and education institutions existing and working in municipalities.